2012
DOI: 10.1111/j.1751-0813.2012.00961.x
|View full text |Cite
|
Sign up to set email alerts
|

Multisite randomised controlled trial to evaluate polypropylene clips applied to the breech of lambs as an alternative to mulesing. I: effects on body weight, breech bare area measurements and scores, wrinkle scores and faecal and urine staining

Abstract: Polypropylene clips applied to the breech and tail of lambs increased breech bare area and reduced dag, urine and wrinkle scores. Improvements in these measures of factors that predispose to blowfly strike suggest that the application of clips may reduce the risk of breech flystrike.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 11 publications
0
11
1
Order By: Relevance
“…The involvement of PETA who threatened an international boycott of wool from mulesed sheep in 2004 was merely the final act of a long building issue (128). The response of the industry in 2004 was to fund research into a limited range of alternatives to mulesing (129), this amounted to other methods of performing the same operation (130) and an analysis of breeding options to select plain bodied sheep (131), more recently selection for blowfly resistance has joined the list (29), although both these genetic options are obviously long term. As a result, the declaration by the Australian Wool Corporation that they would stop mulesing by 2010 has not been achieved and the boycotts are extending (16).…”
Section: Resultsmentioning
confidence: 98%
“…The involvement of PETA who threatened an international boycott of wool from mulesed sheep in 2004 was merely the final act of a long building issue (128). The response of the industry in 2004 was to fund research into a limited range of alternatives to mulesing (129), this amounted to other methods of performing the same operation (130) and an analysis of breeding options to select plain bodied sheep (131), more recently selection for blowfly resistance has joined the list (29), although both these genetic options are obviously long term. As a result, the declaration by the Australian Wool Corporation that they would stop mulesing by 2010 has not been achieved and the boycotts are extending (16).…”
Section: Resultsmentioning
confidence: 98%
“…For instance, Playford et al (2012) suggested that polypropylene clips applied to the breech of lambs produce scar tissue by necrosis and may reduce the risk of flystrike. It consists of cutting away skin from the perianal region using wool-trimming shears, which causes the formation of scar tissue less prone to get dirty.…”
Section: Good Healthmentioning
confidence: 99%
“…3 The mules operation is carried out on young sheep to reduce their life-long susceptibility to flystrike. 5 The clips cause ischaemic necrosis of the occluded skin and the dead skin sloughs between 2 and 4 weeks later, resulting in increased bare skin in the perineal and tail areas compared with unclipped, unmulesed control lambs [6][7][8][9] and reduced breech wrinkle, dags and urine staining to levels mid-way between those of unclipped, unmulesed controls and mulesed lambs. 5 The clips cause ischaemic necrosis of the occluded skin and the dead skin sloughs between 2 and 4 weeks later, resulting in increased bare skin in the perineal and tail areas compared with unclipped, unmulesed control lambs [6][7][8][9] and reduced breech wrinkle, dags and urine staining to levels mid-way between those of unclipped, unmulesed controls and mulesed lambs.…”
mentioning
confidence: 99%
“…[11][12][13] Studies to date show that clipped lambs have similar behaviour and locomotion as untreated control lambs, cortisol responses that are both lower and less prolonged than those in mulesed lambs, and are 1.5 kg heavier than mulesed lambs 25 days after treatment. 6 In the previous studies, clips were removed from the lambs 10-14 days after application [7][8][9] or remained on the lambs for up to 30 days. 6 In the previous studies, clips were removed from the lambs 10-14 days after application [7][8][9] or remained on the lambs for up to 30 days.…”
mentioning
confidence: 99%
See 1 more Smart Citation